2014
DOI: 10.3390/rs6076604
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Spatial Distribution of Culicoides imicola: Climatic versus Remote Sensing Data

Abstract: Culicoides imicola is the main vector of the bluetongue virus in the Mediterranean Basin. Spatial distribution models for this species traditionally employ either climatic data or remotely sensed data, or a combination of both. Until now, however, no studies compared the accuracies of C. imicola distribution models based on climatic versus remote sensing data, even though remotely sensed datasets may offer advantages over climatic datasets with respect to spatial and temporal resolution. This study performs su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To determine which environmental variables most influence the distribution of C. imicola , the main vector of BT in Tunisia, we included 12 bioclimatic variables in our model ( Table 1 ). The selection of environmental and climatic predictors used in the analysis was based on the literature review and association already proved with the disease (Calvete et al 2009 ; Ciss et al 2019 ; Van Doninck et al 2014 ). The bioclimatic data, with a spatial resolution of 30 arc seconds (~1 kilometres [km]), were downloaded from the World Climate website ( http://www.worldclim.org/current ) and averaged over a 50 year period between 1950 and 2000 at the same spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine which environmental variables most influence the distribution of C. imicola , the main vector of BT in Tunisia, we included 12 bioclimatic variables in our model ( Table 1 ). The selection of environmental and climatic predictors used in the analysis was based on the literature review and association already proved with the disease (Calvete et al 2009 ; Ciss et al 2019 ; Van Doninck et al 2014 ). The bioclimatic data, with a spatial resolution of 30 arc seconds (~1 kilometres [km]), were downloaded from the World Climate website ( http://www.worldclim.org/current ) and averaged over a 50 year period between 1950 and 2000 at the same spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of environmental and climatic predictors used in the analysis was based on the literature review and association already proved with the disease (Calvete et al 2009;Ciss et al 2019;Van Doninck et al 2014…”
Section: Bioclimatic Variablementioning
confidence: 99%
“…Machine learning techniques combined with environmental predictors have been used in modelling biting midges ( Culicoides sp.) [30-33], and mosquitoes [28,34,35], and studies on ticks include modelling tick distribution or abundance [36-38] as well as the distribution of tick-borne human diseases [15,39].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of C. imicola is highly dependent on-air temperature, a major limiting factor. However, the precise mechanism of this dependency is not yet known ( Van Doninck et al ., 2014 ). Previously conducted laboratory studies revealed that vector competence varies with temperature and infecting BTV serotype.…”
Section: Discussionmentioning
confidence: 99%